E-Commerce and Consumer Behavior: A Comparative Study of Local and Global Marketplaces in Indonesia - Septien Dwi Savandha (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
The development of e-commerce in Indonesia has driven significant changes in consumer behavior. Local marketplaces such as Tokopedia, Shopee, and Bukalapak compete fiercely with global marketplaces such as Amazon, eBay, and AliExpress. This study aims to: (1) compare consumer behavior in local and global marketplaces, (2) identify the main factors influencing consumer preferences, and (3) analyze the impact of trust variables, security, product variation, and service quality on purchase decisions. The method used is qualitative research with a comparative study approach. Data was collected through in-depth interviews, observations, and documentation, then analyzed with Miles and Huberman's interactive model. The results show that trust and transaction security are the most dominant factors in influencing purchase decisions, followed by ease of use and quality of customer service. Local marketplaces are superior in terms of trust and convenience of transactions, while global marketplaces are stronger in product variety. The conclusion of this study is that Indonesian consumer behavior is more determined by trust and security factors, not just product or price variation. The practical implication is that local marketplaces need to expand product variety to be more competitive, while global marketplaces need to adapt payment methods and customer service according to the needs of Indonesian consumers.